Immunohistochemical expression of CD44s in renal cell carcinoma lacks independent prognostic significance - Costa,Walter Henriques da (2012)
PURPOSE: To analyze the immunohistochemical expression of the standard isoform of CD44 (CD44s) adhesion molecule in clear cell renal cell carcinoma (CCRCC) and its impact on clinical outcomes. MATERIALS AND METHODS: Ninety-nine consecutive patients treated surgically for RCC between 1992 and 2009 were selected. A single pathologist reviewed all cases to effect a uniform reclassification and determine the most representative tumor areas for construction of a tissue microarray. The same pathologist, who was blinded to the outcome of the cases, semi-quantitatively scored the staining intensity of CD44s in all specimens. The counting was done using the H-Score algorithm. RESULTS: Of the 99 immunostained RCC specimens, 57(57.7%) showed low expression, and 42(42.4%) showed high expression levels of CD44s. The expression of CD44s was directly associated with tumor size (p = 0.03), clinical stage (p = 0.02) and Fuhrman grade (p = 0.02). Disease specific survival (DSS) rates for patients whose specimens expressed low and high levels of CD44s was 88.1% and 67.5%, respectively (p = 0.009). Progression free survival (PFS) rates in patients with low and high expression of CD44s were 78.8% and 61.7%, respectively (p = 0.05). Classical features such as the presence of metastasis and clinical stage remained isolated predictors of survival. CONCLUSIONS: Immunohistochemical expression of CD44s was associated with important clinical variables such as stage and Fuhrman grade. However, it was not an independent predictor of survival. Therefore, we believe it has a limited role as a prognostic marker in patients with CCRCC.